Budget impact analysis of subcutaneous trastuzumab compared to intravenous trastuzumab in Saudi HER2-positive breast cancer patients. (4th May 2021) - Elsamany, Shereef; Elsisi, Gihan Hamdy; Hassanin, Fayza; Jafal, Mohamed
ABSTRACT: Background : This study was aimed to assess the budget impact of SC trastuzumab compared to IV trastuzumab in patients with HER2-positive breast cancer (BC) from the perspective of the governmental health sector in Saudi Arabia, over a 3-year time horizon. Methods : A model was developed to calculate the direct medical and indirect costs for 394 incidents HER2-positive BC patients per year who would receive SC trastuzumab compared to IV formulation. We calculated drug acquisition costs for fixed, loading, and subsequent doses of trastuzumab. One-way sensitivity analysis was conducted. Results : Two scenarios were modeled: the first scenario evaluated the impact of gradual replacement of IV formulation by SC, the second scenario, evaluated impact of totally replacing IV formulation. The total annual costs in the first scenario were estimated to be SAR 177 million (USD 98 million) for IV trastuzumab compared to SAR 143 million (USD 79 million) for SC formulation, leading to a total budget saving of SAR 34, 527, 346 (USD 19, 181, 858). In the second scenario, the total annual costs were estimated to be SAR 108 million (USD 60 million) for SC trastuzumab compared to SAR 177 million (USD 98 million) for IV formulation, leading to budget savings of SAR 69, 054, 692 (USD 36, 363, 717). Conclusion : Benefits of the SC formulation over IV infusions are being converted to realistic monetary benefits for all providers and payers.